ANALYSIS OF COMMERCIAL FEEDING WITH A MIXTURES OF HERMETIA ILLUCENS L. AND CORN FODDER (ZEA MAYS L.) ON GROWTH OF PEKING DUCK (ANAS PLATYRHYNCHOS DOMESTICUS) - Ardhya Dirgantini, Regita
The consumption of animal products is increasing one meat as the fulfillment of the requirement for protein. One source of animal protein, Peking duck with the phase of growth relatively quickly. However, one of the problems is the high level of dependence on the consumption of commercial feed. Commercial feed as the main source of protein derived from fish meal and soy flour availability limited cause for the high price. These problems can be solved by performing a combination of feed mixture of bran, corn fodder, and the larvae of the Black Soldier Fly (BSF). It can reduce the cost of feed that reaches 60-70% of the total production cost. This study aims to analyze the effect of five compositions of the feed, P1 (100% commercial feed BR2 Missouri), P2 (50% commercial feed BR2 Missouri + 50% bran), P3 (50% commercial feed BR2 Missouri + 25% bran + 25% BSF), P4 (40% commercial feed BR2 Missouri + 20% bran + 20% corn fodder + 20% BSF), and P5 (50% commercial feed BR2 Missouri + 25% bran + 25% corn fodder) on growth of Peking duck based on the parameters of Weight Gain (WG), Average Daily Gain (ADG), Relative Consumption Ratio (RCR), Relative Growth Rate (RGR), and Final Body Weight (FBW). This research was conducted in the Village of Jatiendah, Kecamatan Cilengkrang, Bandung Regency. The Data obtained were analyzed using the software IBM SPSS Statistics 28. The results showed treatment of 40% commercial feed (BR2 Missouri), 20% bran, 20% of the larvae of the BSF, and 20% of corn fodder (P4) was effective in improving the growth of Peking duck.